Risk factors related to low-level viraemia in chronic hepatitis B patients receiving entecavir treatment - Li, Zhong-Bin; Chen, Dan-Dan; Jia, Yun-Fei; He, Qing-Juan; Cui, Li; Du, Feng-Xia; Kang, Yao-Jie; Feng, Xin; He, Mengwen; Jin, Xue-Yuan; Chen, Jing; Wang, Yudong (Frontiers in Cellular and Infection Microbiology, 2024)
BackgroundAbout 20% of on-treatment patients with chronic hepatitis B (CHB) experienced low-level viraemia (LLV), which is associated with persistent low-grade inflammation, fibrosis progression, and increased risk of hepatocellular carcinoma. We aimed to investigate the high-risk factors related to LLV.MethodsIn this retrospective study, patients receiving entecavir (ETV) treatment from January 2018 to January 2023 were enrolled, and were divided into a LLV (HBV DNA 20-2000 IU/mL) cohort and a complete virological response (CVR) (HBV DNA < 20 IU/mL) cohort according to the virological response at week 48 posttreatment. Treatment baseline characteristics were retrieved from electronic medical records. Multivariate logistic regression was performed.ResultsTotally, 1653 patients were enrolled, male patients accounted for 73.0%; the median age was 44 years; the mean HBV DNA level was 5.9 Log10 IU/ml. Among them, 472 (28.6%) experienced LLV. Multivariate analysis showed that HBeAg positivity (OR = 2.650, 95% CI: 2.000-3.511, p < 0.001), HBV DNA ≥ 6.0 Log10 IU/mL (OR = 1.370, 95% CI: 1.054-1.780, p = 0.019), qHBsAg ≥ 9000 IU/mL (OR = 4.472, 95% CI: 3.410-5.866, p < 0.001), cirrhosis (OR = 1.650, 95% CI: 1.234-2.207, P = 0.001), LSM ≥ 13.0 kPa (OR = 1.644, 95% CI: 1.203-2.246, p = 0.002), and PLT < 100×109/L (OR = 1.450, 95% CI: 1.094-1.922, p = 0.010) at baseline were related to the development of LLV.ConclusionsHigh HBV DNA/HBsAg quantification/LSM, low PLT, HBeAg positivity, and liver cirrhosis were high-risk factors associated with LLV in patients receiving entecavir treatment.